G294(P) Exploring difficulties in child protection practice. A West Midlands survey. (27th April 2016) - Aldaleel, O Kasim; Goodyear, H; Ahmed, E; Ibrahim, F; Mshelbwala, H; Muammar, T
Abstract : Introduction: Doctors and relevant professionals should have appropriate training to be able to protect vulnerable children. For best outcome, local policies need to be in place with optimisation of multiagency team support. Aim: To identify difficulties in children safeguarding practice among doctors regarding training adequacy, confidence in recognition and response, and the support received from the multiagency system. Method: A questionnaire based survey was carried out in the West Midlands-UK, of junior paediatricians, general practitioners and emergency doctors. Results: 141 questionnaire from more than 14 hospitals/practices were analysed, of which 93 (66%) were of junior paediatricians and 48 (34%) were of general practitioners and emergency doctors. Only 5 (3.5%) did not have appropriate child protection training. However, 13% thought that the training did not meet their needs. On a scale of 1–6 (1= not confident at all; 6= very confident), doctors expressed their ability to recognise signs of physical abuse (Mean 4.48 and SD 0.87), factitious illness (Mean 3.36 and SD 1.03), emotional abuse (Mean 3.68 and SD 1.02), and neglect (Mean 4.14 and SD 0.97). Overall, 86% of doctors have confidence to initiate child protection process when they have concerns. There was however significant difference between paediatric and non-paediatric groups in the degree of confidence to initiate the process (p < 0.001). Overall, 50% (n = 71) would wait for a senior opinion before initiating the process. The degree of perceived support by seniors and other members of the multiagency system was variable between doctors groups. On a scale of 1–6 (1= not supported; 6= very supported), it ranged from 3.50–4.45 (Mean 4.21 and SD 2.0). Support by multiagency team members, in normal working hours and out of hours showed some differences. Conclusion: Although child protection training is mandatory, some junior doctors and trainees might need more support. Senior advice is essential, but caution is needed to avoid referrals delay. More trained staff would reduce variation of multiagency team support out of hours. Bigger and possibly national studies on this matter, with inclusion of sexual abuse, are recommended.